2021
DOI: 10.7717/peerj.11953
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear genetic diversity and notable population differentiation caused by low gene flow of bermudagrass [Cynodon dactylon(L.) Pers.] along longitude gradients

Abstract: Background Environmental variation related to ecological habitat is the main driver of plant adaptive divergence. Longitude plays an important role in the formation of plant population structure, indicating that environmental differentiation can significantly shape population structure. Methods Genetic diversity and population genetic structure were estimated using 105 expressed sequence tag-derived simple sequence repeat (EST-SSR) loci. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 88 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…A study of the population structure of 296 bermudagrass genotypes from different latitudes using 153 EST-SSR markers reported more genetic diversity in higher ploidy levels and lower latitudes in China (Zhang et al 2019), and that the population structure follows latitudes with notable admixtures and no isolation by distance. A recent genetic diversity and population structure study of common bermudagrass collection using EST-SSR markers reported notable population differentiation along longitude gradients caused by low gene flow (Zhang et al 2021). The population structure along the latitude gradient implies the existence of genetic variation for cold adaptation among bermudagrass germplasm, whereas the longitudinal gradient implies population isolation.…”
Section: Resultsmentioning
confidence: 99%
“…A study of the population structure of 296 bermudagrass genotypes from different latitudes using 153 EST-SSR markers reported more genetic diversity in higher ploidy levels and lower latitudes in China (Zhang et al 2019), and that the population structure follows latitudes with notable admixtures and no isolation by distance. A recent genetic diversity and population structure study of common bermudagrass collection using EST-SSR markers reported notable population differentiation along longitude gradients caused by low gene flow (Zhang et al 2021). The population structure along the latitude gradient implies the existence of genetic variation for cold adaptation among bermudagrass germplasm, whereas the longitudinal gradient implies population isolation.…”
Section: Resultsmentioning
confidence: 99%
“…They also reported population structure to follow latitudes with notable admixture and no isolation by distance. A recent genetic diversity and population structure study of common bermudagrass collection using EST-SSR markers reported notable population differentiation along longitude gradients caused by low gene flow [45]. The population structure along the latitude gradient implies the existence of genetic variation for cold adaptation among bermudagrass germplasm while the longitudinal gradient implies population isolation.…”
Section: Genetic Diversity and Relatednessmentioning
confidence: 99%
“…They also reported that environments with higher temperatures and high precipitation rates could favor higher rates of variability within populations; but if there is a low gene flow rate, this variability could be exhausted over time. Zhang et al (2021), using 105 EST-SSRs, reported low gene flow, with rich genetic differentiation, among populations of C. dactylon along longitude gradients. The authors stated there was no clear linear trend of intra-population genetic diversity along longitude, and the intra-population genetic diversity was not related to climate.…”
Section: Introductionmentioning
confidence: 98%